Boron doping effect on the structural, spectral properties and charge transfer mechanism of orthorhombic tungsten bronze β-SrTa2O6:Eu3+ phosphor. Issue 18 (20th April 2023) - İlhan, Mustafa and Güleryüz, Lütfiye Feray
Abstract : In the study, the effect of boron doping on spectral properties and CTB mechanism was investigated by using Eu 3+ doped orthorhombic β-SrTa2 O6 . Abstract : In the study, the effect of boron doping on spectral properties and CTB mechanism was investigated by using Eu 3+ doped orthorhombic β-SrTa2 O6 . A phosphor series of Eu 3+ doped SrTa2 O6, and Eu 3+ and B 3+ co-doped SrTa2 O6 polycrystals were fabricated by solid-state reaction at 1400 °C for 20 h in an air atmosphere. The X-ray diffractions of the main phase structure for all the ceramics maintained up to 10 mol% Eu 3+ concentration, while the increase of XRD intensity for Eu 3+ and B 3+ co-doped samples was attributed to somewhat improvement of crystallization. SEM morphologies of grains showed that the presence of boron promotes agglomeration and grain growth. The doping of boron up to 20 mol% led to an increase in PL intensity, CTB energy slightly shifted to low energy, and also an increase occurred in the asymmetry ratio of the phosphor. Therefore, the low crystal field symmetry of the Eu 3+ sites and some improvement in crystal structure properties for Eu 3+, B 3+ co-doped samples supported the PL increase. The trend of Judd–Ofelt parameters ( Ω 2, Ω 4 ) is SrTa2 O6 : x Eu 3+, 0.1B 3+ > SrTa2 O6 : x Eu 3+ . The high Ω 2 parameter for boron co-doped samples showed a covalent Eu–O bond character with low symmetry of Eu 3+ environment, while the high Ω 4 value indicated the reduction in electron density of the ligands. Some increase in the short decays of Eu 3+, B 3+ co-doped samples is probably due to the surface effect and low crystal field symmetry. The quantum efficiency of 0.05Eu 3+, 0.1B 3+ co-doped phosphor with the highest PL intensity increased by about 21% compared to that without boron.